Pengaruh Pengeluaran Pemerintah, Pertumbuhan Ekonomi dan Inflasi, Terhadap Tingkat Kemiskinan di Sumatra Utara - Santi Monika Sagala; Puti Andiny; Safuridar Safuridar; Yani Rizal (Universitas 17 Agustus 1945 Semarang, 2024)
This research aims to analyze the influence of government spending, economic growth and inflation on poverty levels in North Sumatra Province during the 2014-2023 period. Using a quantitative approach with secondary data from the Central Statistics Agency (BPS), this research applies multiple linear regression analysis to identify the variables that have the most influence on poverty. The results of the analysis show that increased government spending, recovered economic growth, and good inflation management contributed significantly to reducing poverty levels, with government spending increasing from 7,808.56 billion rupiah in 2014 to 14,323.52 billion rupiah in 2023. Model The regression shows that these variables influence poverty by 70.19%, while 29.81% is influenced by other factors. This research emphasizes the importance of monitoring and adjusting economic policies to achieve the goal of poverty alleviation more effectively.